(untitled) (Collection of scientific works «Scientific Problems of Architecture and Urban Planning» | ODABA, 2025)
The article is devoted to the study of the dynamics of the development of spatial archetypes in the transition to technocivilization. Particular attention is paid to finding new approaches to the development of historic cities and their centers, ideological and methodological foundations of preservation of architectural monuments, as well as historical and architectural heritage, its use and development in a foreign, ie man-made environment and globalization. It was found that the main trends in solving the problems of coexistence, on the one hand, the urban environment and urban culture, and on the other - the urban environment and mass culture today are associated with several trends in the development of artificial environments. Among them, the most important are the processes of first confrontation and polarization, and then confrontation and absorption by the urban environment of the urban environment. It is proved that the attractiveness of cities is determined by the unconditional advantages of urban life, which increases the pace of socio-cultural development of modern society. The development of the concept of architectural space as a dynamic system and the identification of its humanitarian basis, which through architecture is invariably translated into the environment of human existence within the framework of any social system - from traditional to man-made.